PEMBUATAN GAME 3D HORROR ESCAPE ROOM “THINK OR RUN ?” PADA PLATFORM ANDROID - Vincent Vincent; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
"Think or Run?" is a 3D game with the Horror genre on the Android platform. This game was designed by Unity as a game engine with the C# programming language. The game has 15 stages consisting of a word puzzle stage and a question and answer stage. The concept of this game is that players must complete each stage to continue to the next stage. The controls used in this game are gyroscope sensors. Testing was carried out by conducting the Blackbox, alpha, and beta testing through a questionnaire filled by 35 respondents. The results show that the game has high-difficulty and quite creepy with unique control.